Exploring the state of evidence on aging with HIV in long-term care: A scoping review protocol - Kristina M. Kokorelias; Soo Chan Carusone; Christine Sheppard; Andrew D. Eaton; Cynthia Chui; Dean Valentine; Michael Kirk; Luxey Sirisegaram (PLoS ONE, 2025)
Background The growing population of older adults living with HIV presents unique challenges for long-term care facilities, which are increasingly tasked with supporting residents who require both HIV-specific and geriatric care. Despite advances in HIV treatment that have extended life expectancy, the needs of these individuals in long-term care remain underexplored, and the field lacks a consolidated understanding of how facilities are currently equipped to manage these complexities. This scoping review protocol outlines the approach for synthesizing existing evidence on the experiences, challenges, and care outcomes of aging with HIV in long-term care settings. Objective To examine the state of evidence on older adults with HIV in long-term care, providing an overview of current knowledge on the health, social, and systemic factors influencing their care and identifying gaps that may guide future research and practice. Methods The team includes knowledge users, including experts by experience, to ensure the findings are grounded in lived realities and practical applicability. Using a scoping review framework by the Joanna Briggs Institute, we will conduct a comprehensive search of literature from inception in the following electronic databases: MEDLINE (R) ALL (Ovid), Embase Classic + Embase (Ovid), Cochrane Central Register of Controlled Trials (Ovid), CINAHL Ultimate (EBSCO), PsycINFO (Ovid), AgeLine (EBSCO), and Scopus to capture studies that address aging with HIV in long-term care settings. Eligible studies will be screened and selected based on criteria focused on relevance to the intersection of aging, HIV, and long-term care. Articles will be screened by two reviewers. Data will be charted and synthesized thematically, allowing for an organized summary of findings on key topics such as physical and mental health, care provision, and facility preparedness. Discussion and implications This review will offer an overview of the current state of knowledge on aging with HIV in long-term care facilities, highlighting what is known about care practices, health outcomes, and systemic challenges in these settings. Findings will clarify the breadth and depth of existing evidence and reveal areas requiring further research, thereby informing policy and enhancing care strategies for this population.